Sealing Glass‐Ceramics with Near‐Linear Thermal Strain, Part II: Sequence of Crystallization and Phase Stability. Issue 11 (22nd August 2016) - Rodriguez, Mark A.; Griego, James J. M.; Dai, Steve
Abstract : The sequence of crystallization in a recrystallizable lithium silicate sealing glass‐ceramic Li2 O–SiO2 –Al2 O3 –K2 O–B2 O3 –P2 O5 –ZnO was analyzed by in situ high‐temperature X‐ray diffraction (HTXRD). Glass‐ceramic specimens have been subjected to a two‐stage heat‐treatment schedule, including rapid cooling from sealing temperature to a first hold temperature 650°C, followed by heating to a second hold temperature of 810°C. Notable growth and saturation of Quartz was observed at 650°C (first hold). Cristobalite crystallized at the second hold temperature of 810°C, growing from the residual glass rather than converting from the Quartz. The coexistence of quartz and cristobalite resulted in a glass‐ceramic having a near‐linear thermal strain, as opposed to the highly nonlinear glass‐ceramic where the cristobalite is the dominant silica crystalline phase. HTXRD was also performed to analyze the inversion and phase stability of the two types of fully crystallized glass‐ceramics. While the inversion in cristobalite resembles the character of a first‐order displacive phase transformation, i.e., step changes in lattice parameters and thermal hysteresis in the transition temperature, the inversion in quartz appears more diffuse and occurs over a much broader temperature range. Localized tensile stresses on quartz and possible solid‐solution effects have been attributed to the transition behavior of quartz crystals embedded in the glass‐ceramics.